Pronunciation of Hijaiyyah’s letter for New Quranic Learners a Contrastive Analysis Study - Yuslina Mohamed; Sulaiman Ismail; Yoke Suryadama (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah: Malaysian Journal of Islamic Sciences Volume 36 Issue 1 Page (73-82)